Cell surface polysaccharides from Bradyrhizobium japonicum and a nonnodulating mutant. - Puvanesarajah, V (1987)
The cell surface polysaccharides of wild-type Bradyrhizobium japonicum USDA 110 and a nonnodulating mutant, strain HS123, were analyzed. The capsular polysaccharide (CPS) and exopolysaccharide (EPS) of the wild type and the mutant strain do not differ in their sugar composition. CPS and EPS are composed of mannose, 4-O-methylgalactose/galactose, glucose, and galacturonic acid in a ratio of 1:1:2:1, respectively. H nuclear magnetic resonance spectra of the EPS and CPS of the wild type and mutant strain are very similar, but not identical, suggesting minor structural variation in these polysaccharides. The lipopolysaccharides (LPS) of the above two strains were purified, and their compositions were determined. Gross differences in the chemical compositions of the two LPS were observed. Chemical and sodium dodecyl sulfate-polyacrylamide gel electrophoresis analyses indicated that strain HS123 is a rough-type mutant lacking a complete LPS. The LPS of mutant strain HS123 is composed of mannose, glucose, glucosamine, 2-keto-3-deoxyoctulosonic acid, and lipid A. The wild-type LPS is composed of fucose, xylose, arabinose, mannose, glucose, fucosamine, quinovosamine, glucosamine, uronic acid, 2-keto-3-deoxyoctulosonic acid, and lipid A. Preliminary sugar analysis of lipid A from B. japonicum identified mannose, while traces of glucosamine were detected. 3-Hydroxydodecanoic and 3-hydroxytetradecanoic acids formed a major portion of the fatty acids in lipid A. Lesser quantities of nonhydroxylated 16:0, 18:0, 22:0, and 24:0 acids also were detected.